Ekstraksi Antosianin Pada Bunga Telang - Muhammad Rifqi Suryana (Pasundan Food Technology Journal (PFTJ), 2021)
Anthocyanin is a compound that forms natural dyes in plants in giving colors orange, red, and purple. Anthocyanins can be found in red, purple, dark red plants such as berries and ornamental plants such as Butterfly pea (Clitoria ternatea). Butterfly pea (Clitoria ternatea) have a high enough potential for the food industry including being used as food coloring and used as traditional medicine. Process extraction anthocyanin of Butterfly pea (Clitoria ternatea) using different methods produces extracts with different total anthocyanins. In the future, further research is needed to be able to extract anthocyanin in telang flowers to produce an extract with high total anthocyanin and not easily damaged.